A cross-sectional study examining the association between MRCS performance and surgeons receiving sanctions against their medical registration. Issue 4 (August 2022) - Ellis, R.; Cleland, J.; Scrimgeour, D.S.G.; Lee, A.J.; Brennan, P.A.
Abstract: Background: Fitness to practice (FtP) investigations by the General Medical Council (GMC) safeguard patients and maintain the integrity of the medical profession. The likelihood of FtP sanctions is influenced by specialty and socio-demographic factors and can be predicted by performance at postgraduate examinations. This is the first study to characterise the prevalence of FtP sanctions in early-career surgeons and to examine the association with performance at the Membership of the Royal College of Surgeons (MRCS) examination. Methods: All UK graduates who attempted MRCS between September 2007–January 2020 were matched to the GMC list of registered medical practitioners. Clinicians who had active FtP sanctions between 28th August 2018 and 28th August 2020 were identified. Data were anonymised by RCS England prior to analysis. Results: Of 11, 660 candidates who attempted MRCS within the study period, only 31 (0.3%) had FtP sanctions between 2018 and 2020. Of these, 12 had active conditions on registration, seven had undertakings and 14 had warnings. There was no statistically significant difference in MRCS performance in either Parts A or B of the examination for those with and those free from FtP sanctions (P > 0.05). Conclusions: In this, the largest study of MRCS candidates to date, the prevalence of active FtP sanctions in early-career surgeons was 0.3%, significantly lower than the prevalence of sanctions across more experienced UK surgeons (0.9%). These data highlight early-career surgeons as a low-risk group for disciplinary action and should reassure patients and medical professionals of the rarity of FtP sanctions. Highlights: This was the largest study of MRCS candidates to date (n = 11, 660). The prevalence of GMC Fitness to Practice sanctions in early-career surgeons was 0.3%. This is lower than the prevalence of sanctions in more experienced surgeons (0.9%). Early-career surgeons are a low-risk group for disciplinary action. It cannot be stated that MRCS performance predicts future disciplinary action.